The Consulate General of the Republic of Poland in Vilnius (1991–2008) – History of the Consular Mission and Actions for Polish Education and Culture in Lithuania - Kamilewicz-Rucińska, Danuta (Studia Warmińskie, 2024)
The Consulate General of the Republic of Poland in Vilnius, as an independent diplomatic mission, operated for 17 years (1991–2008). In the context of the host country – Lithuania – the Polish national minority not only makes up the highest percentage, but also maintains a strong presence as a lively community that proudly identifies with their Polish heritage, its presence was exceptionally important, challenging, and necessary. In line with the provisions of Polish law, international law, European Union law, and international customs, the Consulate General in Vilnius, acting in support of Polish education and culture in Lithuania: undertook actions to strengthen ties between the Republic of Poland and individuals of Polish descent or declaring affiliation with the Polish Nation residing in Lithuania; worked towards the interests of the Polish national minority and the rights and freedoms of individuals belonging to this minority; supervised, within its competence, the implementation of international agreements; through cooperation with Polish organizations, associations, as well as individual entities, developed and deepened economic, scientific, technical, and cultural cooperation between the Republic of Poland and Lithuania. Currently, all activities aimed at Polish culture, education, schooling, and the Polish language in Lithuania have been taken over by the Embassy of the Republic of Poland in Vilnius. The Consulate General, functioning as an independent administrative entity, played a vital role in advocating for the rights of the Polish minority in Lithuania. It served as an important and necessary voice, reflecting the concern of Polish diplomacy towards efforts to provide education to the Polish national minority in their native language. It contributed to enhancing the overall well-being of Poles in Lithuania.